CIVIL DISPUTE OVER OWNERSHIP OF DIGITAL ASSETS NON-FUNGIBLE TOKENS (NFTS) - Pradipta, Aryadipa Raditya; Putri, Rosa Diga (Fakultas Hukum Universitas Swadaya Gunung Jati, 2026)
The transnational nature of Non-Fungible Tokens (NFTs) presents complex jurisdictional challenges in civil dispute resolution that transcend national boundaries. This research examines NFT ownership disputes through the lens of Private International Law, analyzing choice-of-laws, forum selection, and recognition of foreign judgments. Employing a normative legal research methodology with comparative and case-study approaches, this study investigates jurisdictional frameworks, the determination of applicable law, and cross-border enforcement mechanisms. The findings reveal that the decentralized, borderless nature of blockchain technology creates unprecedented conflicts of law, with traditional private international law principles proving inadequate. The study concludes that international harmonization of NFT regulations is essential, requiring multilateral cooperation and the adaptation of conflict-of-laws rules to accommodate the characteristics of digital assets while ensuring predictability and fairness in cross-border dispute resolution.